Strategi UMKM Simpang Karya Dalam Meningkatkan Pendapatan Pasca Pandemi Covid-19 - Rinta Okta Sari; Elyanti Rosmanidar; Nufitri Martaliah; Habriyanto Habriyanto (Lembaga Pengembangan Kinerja Dosen, 2024)
After the Covid-19 pandemic, there is still a big impact on the continuity of UMKM (Micro, Small and Medium Enterprises) businesse Simpang Karya UMKM owners admitted that they had experienced the negative impact of Covid-19 on their business processes, including experiencing a significant decline in sales. This research aims to find out what strategies and what obstacles are faced by Simpang Karya UMKM in increasing income after the Covid-19 pandemic. This research uses a qualitative approach. The data sources used are primary and secondary data sources. Meanwhile, the data collection techniques used in this research are observation, interviews and documentation. The research results show that in terms of strategy, Simpang Karya UMKM have implemented the Marketing Mix concept, namely product, price, promotion and place. Simpang Karya UMKM in running their business also implement sharia marketing strategies. The characteristics of sharia marketing are rabbaniyah, akhlaqiah, al-waqiyah, and insaniyah.